Analysis of frequency dependent Vedic chanting and its influence on neural activity of humans - Veera Raghava Swamy Nalluri; V. J. K. Kishor Sonti; G. Sundari (Institute of Advanced Engineering and Science, 2023)
In this paper a novel methodology is proposed to identify and to compare the frequency range of different Vedic chantings from Rig Veda, Yajur Veda, Atharva Veda and Sama Veda. Nowadays in spite of busy schedule and hectic work, the human beings are mostly stressed. To get rid from this stressed state, one of the best solutions is listening Vedic chantings. The alpha brainwaves are in the frequency range of 8-12 Hz under giving relaxation to stressed human being. Three selected samples from each Veda have been processed through the simulation compiler Praat and the parameters like spectral response, pitch, intensity, formants and pulses have observed. In the above identified parameters, the frequency in intensity calculation is taken for each sample. This frequency is compared with the brainwaves for which the frequencies are in the ranges of 0 Hz to >27 Hz (alpha, beta, gamma, theta and delta). The extracted signal frequencies from Vedic chantings are compared with frequencies of brainwaves. Among the four Vedas, the frequencies extracted from Sama Veda lies in alpha frequency range. The remaining is fluctuating from alpha.